Mathematical Modeling of Covid-19 Model dynamical transmission with different way of infections (Journal of Mathematical Modeling and Fractional Calculus, 2025)
The COVID-19 pandemic is causing a lot of pain on a global scale. This work aims to develop new mathematical models for the outbreak by utilising fractional derivatives. Through the control of certain diseases, the adoption of changed methodologies and fundamental explanations can have a substantial impact on the fitness of society. Examining the dynamics and numerical approxima tions for the suggested arbitrary-order coronavirus illness system is the primary goal. For the Covid-19 model, the study introduces fractional derivatives using sophisticated methods such as the Atangana Baleanu, Sumudu transform, and Atangana-Toufik scheme. These methods yield accurate findings while examining the outbreak. Solutions involving various fractional operators are constructed using the Generalized Mittag-Leffler law. Covid-19 effects at various fractional values are explained and theoretical results are validated using numerical simulations. This aids in comprehending the outbreak and its management tactics.
Keywords: Fractional operators; Sumudu Transform; Qualitative analysis.